Implementasi Metode Konversi Hari Lahir dari Tahun Masehi ke Tahun Hijriah - Khatimah, Husnul; Irwan, Muh.; Fatmawati, (HISABUNA: Jurnal Ilmu Falak, 2023)
Abstrack This article contains the main problem under study, namely how to implement the method of converting birthdays from the Christian year to the Hijri year in Tritiro Village, Bontotiro District, Bulukumba Regency with 3 sub-problems, namely: 1) How is the method used in converting birthdays from the Christian year to the Hijri year in Tritiro Village, Bontotiro District, Bulukumba Regency, 2) How is the result of converting birthdays from the Christian Year to the Hijri Year in Tritiro Village, Bontotiro District, Bulukumba Regency. This research uses field research (field research) which is qualitative in nature, syar'i and astronomical approaches. Primary data sources are; Observations, interviews and secondary data were obtained from books, journals and articles. Data collection through observation, interviews and documentation. This study uses data processing and analysis techniques in the form of; analyze, manage and classify data and provide final conclusions. The results of this study indicate that the method used in converting birthdays from AD to Hijri year in Tritiro Village, Bontotiro District, Bulukumba Regency used is the urfi reckoning and essential reckoning. The results of converting birthdays from AD to Hijri in the six samples are as follows: 1) Lahamuddin was born on March 19, 1957 AD, which coincides with the 18th of Sha'ban 1376 H, which falls on a Wednesday. 2) Hj. Jumorang was born on 28 November 1940 AD to coincide with the 27th Shawwal 1359 H, which falls on a Wednesday. 3) Muslim was born on 03 September 1951 AD to coincide with the 1st of Zulhijjah 1370 H, which falls on a Monday. 4)A. Murni was born on October 8, 1961 AD to coincide with the 28th of Rabiul Akhir 1381 H, which falls on a Monday. 5) Abd. Rahman was born on 21 April 1951 AD to coincide with the 14th Rajab 1370 H, falling on a Saturday. 6) Bau Tanning was born on June 23, 1951 AD to coincide with the 18th of Ramadan 1370 H, which falls on a Saturday. The implication of this research is that it is expected that the government or religious figures broaden their horizons who already understand and understand the conversion of the Christian year to the Hijri year correctly. It is hoped that students, especially the faculties of shari'ah and law and astronomy affairs, will continue to play an important and active role in providing knowledge to the public regarding the steps or procedures for converting birthdays from the Christian year to the Hijri year. Keywords: Conversion of Birthday, Christian Year, Hijri Year